Exploring the driving forces of CO2 emission changes in Chinese cities: A production-theoretical decomposition analysis - Cao, Ruili; Zhao, Zhibo (Frontiers in Environmental Science, 2022)
Analyzing the driving forces of CO2 emissions of cities could provide valuable information for carbon reduction policy-making in China. This study uses an improved production-theoretical decomposition analysis to decompose CO2 emissions for 282 cities in China during 2003-2017. The empirical results show that the scale effect, energy intensity effect, and desirable output productivity effect contributed to about 15.03%, 3.64%, and 2.3% of the growth in CO2 emissions on average, respectively, while potential CO2 emission effect and undesirable output productivity effect were responsible for 5.81% and 5.72% of the fall in CO2 emissions. By classifying the sample cities and further analyzing them, it is found that the potential CO2 emission effect has a stronger inhibitory impact in resource-based cities. Whereas, the promoting effect of scale effect is more obvious in non-resource-based cities. From a spatial distribution perspective, the potential CO2 emission effect is a more obvious inhibiting role, and the energy intensity effect is a strong measure to control the growth of CO2 emissions in the eastern region. However, the contribution of the scale effect to CO2 emissions is more pronounced in the western region. In addition, we also find that the desirable output productivity effect has a suppressive effect in the eastern region and a facilitating effect in the central and western regions. The undesirable output productivity effect has a suppressive effect on the growth of CO2 emissions in all three regions, but the suppressive effect is more pronounced in the eastern region.